2023
DOI: 10.1126/sciadv.adg5858
|View full text |Cite
|
Sign up to set email alerts
|

Periplasmic biomineralization for semi-artificial photosynthesis

Abstract: Semiconductor-based biointerfaces are typically established either on the surface of the plasma membrane or within the cytoplasm. In Gram-negative bacteria, the periplasmic space, characterized by its confinement and the presence of numerous enzymes and peptidoglycans, offers additional opportunities for biomineralization, allowing for nongenetic modulation interfaces. We demonstrate semiconductor nanocluster precipitation containing single- and multiple-metal elements within the periplasm, as observed through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…(f) Malate production in E. coli with CdS nanoclusters increases significantly under light compared to dark conditions. Panels d–f are adapted with permission from ref . Copyright 2023 American Association for the Advancement of Science.…”
Section: Perspective For Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(f) Malate production in E. coli with CdS nanoclusters increases significantly under light compared to dark conditions. Panels d–f are adapted with permission from ref . Copyright 2023 American Association for the Advancement of Science.…”
Section: Perspective For Future Directionsmentioning
confidence: 99%
“…The field of biomineralization offers new opportunities. Recent achievements in semiartificial photosynthesis (Figures 5d−f) through periplasmic biomineralization within Escherichia coli cells 53 have set the stage for the in situ formation of semiconductor-based biointerfaces. These insights indicate the potential of harnessing the inherent properties of neurons and glial cells to create dynamic, adaptive nanostructured interfaces, potentially eliminating the necessity for genetic modifications.…”
Section: ■ Perspective For Future Directions Drawing Inspiration From...mentioning
confidence: 99%
“…For whole-cell hybrid photocatalysis, nanoparticles act as solar energy receivers, and living organisms provide catalytic sites. It has been demonstrated that photoelectrons generated from surface-anchored CdS semiconductors or periplasmic biomineralized CdS nanoclusters could be directly transported into cytoplasmic enzymes for photocatalysis via redox membrane-binding proteins 4 , 9 . The coupling performance is partly governed by the balance between photoelectron generation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Through the combination of light-harvesting nanostructures with redox enzymes, several groups have developed photobiocatalytic or photobioelectrocatalytic processes to fix CO 2 /N 2 into complex chemicals with high specificity. These studies have provided valuable insights into photosensitization or charge-injection-driven biocatalysis that can utilize renewable photons as redox equivalents to replace the natural, high-cost biological redox sources. Furthermore, photosensitization of live bacteria (nanobiohybrids or nanorgs) that can directly utilize CO 2 /N 2 has simplified the process of utilizing different energy photons to enable value-added biochemical production with high efficiency and selectivity. …”
Section: Introductionmentioning
confidence: 99%